Tingkat Kesukaan dan Kandungan Zat Gizi Cookies Menggunakan Salak Pondoh (Salacca Zalacca Var Pondoh): Level of Favorite and Nutritional Content of Cookies Using Salak Pondoh (Salacca Zalacca Var Pondoh) - Miftana Fitri Aditami; Maryanto, Sugeng; Puji Afiatna (UNIVERSITAS NGUDI WALUYO, 2024)
Salak fruit is perishable, has a limited shelf life, so it is necessary to use appropriate technology to process snake fruit. Salak processed using simple technology that can last quite a long time is making snake fruit flour. Salak flour is processed into raw materials for making processed products into cookies. The aim of this research was to determine the level of preference and nutritional content in processed salak flour cookies. This research uses an experimental design. The sample used was 25 untrained panelists. This was done by making 4 formulations for each product using salak flour F1 (25%: 75%), F2 (50%: 50%), F3 (75%: 25%), F4 (100%) then carried out a liking test . Next, a nutrient content test is carried out. Analysis of protein, ash, water, fat, carbohydrate and fiber content. The protein content of Pondoh salak cookies is 7.6%, energy 469,615 Kcal, ash 1.60%, water content 4.3%, fat content 19.9%, carbohydrates 64.9%, fiber content 2.8%. The cookie test results based on the highest level of preference were F2 with average values for color (78.4%), aroma (75.3%), taste (77.6%), texture (74.4%). The most popular salak pondoh cookie formula is formula 2 with an average score of 76.4% in the